2020
DOI: 10.1055/a-1119-6616
|View full text |Cite
|
Sign up to set email alerts
|

Peroral endoscopic pyloromyotomy for gastroparesis: a systematic review and meta-analysis

Abstract: Background and aim Gastric peroral endoscopic pyloromyotomy (G-POEM) is a new therapeutic option for refractory gastroparesis (GP). A systematic review and meta-analysis was conducted to assess the effectiveness of G-POEM in refractory GP. For the quality of evidence, we used the Grading of Recommendations Assessment, Development and Evaluation (GRADE) criteria. Methods We performed a literature search using MEDLINE, Embase, Cochrane library, LILACS and the Science citation index for studies related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 46 publications
0
33
0
Order By: Relevance
“…Unfortunately, many have proven to be largely non-effective in achieving this goal 13 . Surgical options like transpyloric stents, pylorotomy or gastrectomy may ameliorate some symptoms, but inevitably curtail the stomach's roles as a digestive organ and reservoir with the risk of severe secondary complications 14 - 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, many have proven to be largely non-effective in achieving this goal 13 . Surgical options like transpyloric stents, pylorotomy or gastrectomy may ameliorate some symptoms, but inevitably curtail the stomach's roles as a digestive organ and reservoir with the risk of severe secondary complications 14 - 17 .…”
Section: Introductionmentioning
confidence: 99%
“…One meta-analysis demonstrated that the pooled mean differences in GCSI scores and the 4-hour solid-phase gastric emptying scintigraphy following single POP were significant at 1.76 and 26.28, respectively, as well as showing POP as having a 71% clinical success rate. [ 18 ] Another recent meta-analysis [ 17 ] revealed that pooled clinical success rates based upon GCSI scores and the 4-hour gastric emptying scintigraphy after single POP were not significant at 75.8% and 85.1%, respectively, when compared to surgical pyloromyotomy. In our study we further prove that double POP may offer better clinical success results than both single POP and LP, with similar recurrence and complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, double POP is performed with 2 circular pyloromyotomies in 1 session when compared to single POP. Recently, 1 systemic review reported improved outcomes in clinical response and gastric emptying scintigraphy regarding POP alone in the treatment of gastroparesis, [ 18 ] thus the application of this datum in clinical practice may be of limited value. Therefore, the aim of this systemic review and meta-analysis was to compare the short-term outcomes surrounding the efficacy, as well as the complication rate between different modalities of pyloromyotomy and GES, in the treatment of gastroparesis.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis demonstrated an overall 100% technical success rate and a 71% clinical success rate. 59 Predictive factors of poor response to treatment include female gender and diabetic gastroparesis. Favorable results are seen in patients with documented EndoFLIP measurements (distensibility, length, cross-sectional area, and pressure) showing pyloric pathology, idiopathic/postsurgical gastroparesis, and those who responded to pyloric stenting/dilation or botox injection.…”
Section: Endoscopic Managementmentioning
confidence: 99%